SINERGISME PENDIDIKAN FORMAL DAN NON-FORMAL DALAM PENGEMBANGAN KEWIRAUSAHAAN: Analisis dan Kajian Layanan Bimbingan Karir di Sekolah - IM Hambali (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2019)
Labor issues and unemployment in Indonesia are currently addressed issues to resolve. Entrepreneurship is an important choice to overcome the number of gap between the workforce who have not worked with job opportunities. The purpose of this study is to describe the themes of experience, skills and attitudes that have been and have not been presented in formal schools, and subsequently become the priority themes to be presented in non-formal education. This research was carried out in a descriptive design, exploratory data collected by means of interviews and interviews, and presented it proportionally, analyzed and with technical processes. The conclusions presented in this article include information about the themes of knowledge, skills and attitudes that have not been widely presented in formal schools, and then presented in non-formal institutions in the form of synergism that complement each other.